Customs Matters : Strengthening Customs Administration in a Changing World - Adams, Debra.; Baer, Katherine (International Monetary Fund, 2022)
Customs administrations around the world face new challenges: an increasing volume of international trade, a revolution in new technologies, and fundamental changes in business models. The benefits of a well-performing customs administration are clear, as is the need to develop efficient, effective, fair, and modern customs administrations. Customs Matters analyzes the many changes and challenges customs administrations face and pro-poses ways to address them. By offering a cross-sectional view of the main aspects of customs ad-ministration, the book guides policymakers and customs officials as they evaluate the current state of their customs system with a view to developing, reinforcing, or relaunching their own roadmaps for customs modernization.